Masa Depan Politik Desentralisasi di Indonesia: Sebuah Studi Awal - Haryanto, Haryanto (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2016)
AbstractPolitical reality in Indonesia tells the relationship between decentralization and democracy, in some respects, problematic. This paper intends to explain the politics of decentralization in Indonesia through a substantive democratic approach. Various studies and scientific research that has been generated, and information of media become the main reference to explain how the future of decentralized Indonesia. This paper concludes how to create procedures to strengthen the achievement of substantive democracy in relation to decentralization. Any offer and strategy, and what is needed to bring the future of a more democratic decentralization.Keywords: decentralizaton, substantive democracy, local politics AbstrakRealita politik di Indonesia menceritakan hubungan antara desentralisasi dan demokrasi, dalam beberapa hal, bermasalah. Tulisan ini bermaksud untuk menjelaskan politik desentralisasi di Indonesia melalui pendekatan demokrasi substantif. Berbagai studi dan riset ilmiah yang telah dihasilkan, maupun informasi media menjadi rujukan utama untuk menjelaskan bagaimana masa depan desentralisasi Indonesia. Tulisan ini kemudian menyimpulkan bagaimana menciptakan prosedur penguatan pencapaian demokrasi subtantif dalam hubungannya dengan desentralisasi. Apa saja tawaran dan strategi, dan apa saja yang dibutuhkan untuk menghadirkan masa depan desentralisasi yang lebih demokratis.Kata kunci: desentralisasi, demokrasi subtantif, politik lokal